HDAC6 mediates an aggresome-like mechanism for NLRP3 and pyrin inflammasome activation - Magupalli, Venkat Giri; Negro, Roberto; Tian, Yuzi; Hauenstein, Arthur V; Di Caprio, Giuseppe; Skillern, Wesley; Deng, Qiufang; Orning, Pontus; Alam, Hasan B; Maliga, Zoltan; Sharif, Humayun; Hu, Jun Jacob; et al. (Science (American Association for the Advancement of Science), 2020)
Inflammasomes are supramolecular complexes that play key roles in immune surveillance. This is accomplished by the activation of inflammatory caspases, which leads to the proteolytic maturation of interleukin 1β (IL-1β) and pyroptosis. Here, we show that nucleotide-binding domain, leucine-rich repeat, and pyrin domain-containing protein 3 (NLRP3)- and pyrin-mediated inflammasome assembly, caspase activation, and IL-1β conversion occur at the microtubule-organizing center (MTOC). Furthermore, the dynein adapter histone deacetylase 6 (HDAC6) is indispensable for the microtubule transport and assembly of these inflammasomes both in vitro and in mice. Because HDAC6 can transport ubiquitinated pathological aggregates to the MTOC for aggresome formation and autophagosomal degradation, its role in NLRP3 and pyrin inflammasome activation also provides an inherent mechanism for the down-regulation of these inflammasomes by autophagy. This work suggests an unexpected parallel between the formation of physiological and pathological aggregates.